Assessing the Environmental and Economic Benefits of Solar Energy Integration in Nigerian Construction. - Unegbu, Hyginus Chidiebere Onyekachi; Yawas, Danjuma S.; B., Dan-asabe; A.A., Alabi (Universitas Teknokrat Indonesia, 2025)
This study investigates the environmental and economic benefits of integrating solar energy into the Nigerian construction sector, alongside the challenges and barriers hindering its adoption. Utilizing a mixed methods approach, the research combines quantitative data from surveys and qualitative insights from interviews and case studies. The findings demonstrate substantial reductions in greenhouse gas emissions and pollutants such as sulfur dioxide and nitrogen oxides, highlighting the positive impact of solar energy on air and water quality. Economically, the analysis reveals high Net Present Values (NPV) and Internal Rates of Return (IRR), indicating that solar energy investments are financially viable with significant long-term savings. However, the study identifies key challenges, including financial constraints, technological limitations, regulatory hurdles, and social and cultural barriers. Hierarchical Linear Modeling (HLM) provides a nuanced understanding of the multi-level factors influencing solar energy adoption, emphasizing the importance of individual awareness and organizational policy support. The study contributes to the existing literature on sustainable construction by providing empirical evidence and practical insights for policymakers and industry stakeholders. Recommendations include the development of supportive regulatory frameworks, financial incentives, public awareness campaigns, and community engagement strategies to overcome the identified barriers. Despite its limitations, this study underscores the critical role of solar energy in promoting environmental sustainability and economic development in Nigeria, calling for coordinated efforts to accelerate the transition to renewable energy solutions.